Pengaruh Dimensi Kualitas Layanan Dan Harga Terhadap Kepuasan Konsumen Toko Bangunan H. Ijul Tabalong - Ahmad Farhani; R.R Yulianti Prihatiningrum (Universitas Lambung Mangkurat, 2022)
This study examines the effect of the dimensions of service quality and price on consumer satisfaction at the H. Ijul Tabalong Building materials store.This study uses six exogenous variables responsiveness, reliability, assurance, tangibles, empathy, and price, while the endogenous variable is customer satisfaction. Sampling was done by purposive sampling totaling 166 respondents.The data analysis technique used Variance Based SEM (PLS-SEM) with SmartPLS software version 3.29. The results showed that the variables of responsiveness, reliability, assurance, and tangible had a positive and significant effect on consumer satisfaction; In contrast, the variables of empathy and price had a negative and insignificant impact on consumer satisfaction at H. Ijul Building Materials Store. Keywords: Dimensions of Service Quality, Price, Consumer Satisfaction, PLS-SEM